16.8k views
3 votes
(x2+4x+8)+ (2x2 +5x+9)

User Lwe
by
5.4k points

1 Answer

8 votes

Answer:


\left(x^2+4x+8\right)+\left(2x^2+5x+9\right)=3x^2+9x+17

Explanation:

Given the expression


\left(x^2+4x+8\right)+\:\left(2x^2\:+5x+9\right)

solving the expression


\left(x^2+4x+8\right)+\:\left(2x^2\:+5x+9\right)

remove the parentheses


\left(x^2+4x+8\right)+\:\left(2x^2\:+5x+9\right)=x^2+4x+8+2x^2+5x+9

Group like terms


=x^2+2x^2+4x+5x+8+9

Add similar elements: x² + 2x² = 3x²


=3x^2+4x+5x+8+9

Add similar elements: 4x + 5x = 9x


=3x^2+9x+8+9


=3x^2+9x+17

Therefore, we conclude that:


\left(x^2+4x+8\right)+\left(2x^2+5x+9\right)=3x^2+9x+17

User PyMaster
by
4.9k points